Effect of CuO antibacterial coating on cotton, polyester, and blend wool fabrics - Hartina, Mohd Yusop; Wan Norfazilah, Wan Ismail; Noreen Farzuhana, Mohd Zulkifli; Saiful Nizam, Tajuddin (Biointerface Research, 2023)
In the present work, the copper oxide nanoparticles (CuO NPs) were successfully synthesized via the sol-gel method to coat on cotton, polyester, and blend wool fabrics. The solution was deposited onto the fabrics by a dip-dry process. The sol-gel synthesis process was confirmed to be successful through the presence of the complex nature of pomegranate rind extract (PRE) in CuO NPs solution as determined by Fourier transform infrared spectroscopy (FTIR) and the existence of copper in all coated fabrics by and dispersive X-ray spectroscopy (EDX) analysis. All the coated fabrics show antibacterial properties towards all three species of gram-positive bacteria, namely Brevibacterium linens, Cutibacterium acnes, and Staphylococcus epidermidis. The maximum inhibition zone was observed at 7 mm on coated blend wool fabric towards B. linens. The CuO-coated fabrics have established good antibacterial properties and could be used in medical textiles and everyday clothing to prevent bacterial infection.